Bodies of nature - Macnaghten, Phil; Urry, John (Published in Association with Theory, Culture & Society., 2001)
This book examines the embodied nature of people's experience in, and of, the modern world. It is therefore part of the deep-seated t̀urn towards the body', which has been such a pronounced feature of sociology in the last two decades. The book argues that bodies in nature are subject to novel, complex and contradictory opportunities of freedom and escape, surveillance and monitoring, and guides readers through the various ways in which these bodily opportunities and constraints are temporally and spatially organized and managed.